1974
DOI: 10.1177/004051757404400310
|View full text |Cite
|
Sign up to set email alerts
|

A Microscopical Survey of Flame-Resistant Cotton Fabrics

Abstract: Three cotton printcloth fabrics treated for flame resistance with THPOH-NHx, oxidized and nonoxidixed, were studied by light microscopy and by transmission (TEM) and scanning (SEM) electron microscopy. Chars of the treated fabrics were also examined. Staining with Acid Blue I and examination by light microscopy provided a semicluantitative assessment of penetration of nonoxidized THPOH-NHa into yarns and fibers, but was less effective with the oxidized sample. SEM observations indicated polymer build-up on fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Scanning electron microscopy (SEM) provides a means for examination at magnifications great enough to see changes in indi-vidual fiber structures, and has been used to study chars of cotton fabrics that had been treated with various flame retardant (FR) agents [3,4,6,7]. Natural and synthetic fibers respond differently to flame retardants and to heat, and thus have different effects on the resulting char.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) provides a means for examination at magnifications great enough to see changes in indi-vidual fiber structures, and has been used to study chars of cotton fabrics that had been treated with various flame retardant (FR) agents [3,4,6,7]. Natural and synthetic fibers respond differently to flame retardants and to heat, and thus have different effects on the resulting char.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of the blisters (nodules) can also be seen. Goynes et al [3] have suggested that the bubbles (nodules) observed on the char of fabric treated with THPOH-NH3 finish could be due to the entrapment of decomposition gases in the coating of ' the fused polymer on the fiber surface. Figure 3 represents a situation where the polymer coating has increased to the extent that formation of nodules can occur.…”
Section: Resultsmentioning
confidence: 99%
“…B Scanning electron microscope (SEM) examinations based on polymeric flame-retardent (FR) finishes have been reported by Goynes et al [3] and Tomioka and co-workers [7]. In these studies the char obtained by burning the fabrics treated with THPOH-NH3 showed the presence of a thick coating, as well as blisters, on the surface.…”
Section: Introductionmentioning
confidence: 93%
“…The formation of such liquid intermediates, which catalyse the char forming, is supported by Goynes et al through electron microscopic evidence. 17 It is likely that the char forms simultaneously through the respective liquid stages of the melt polymer and the liquid intermediates. Therefore, the observed char structure is a consequence of the chemical reactions of flame retardant additives by physical molten mixing.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%